Preparação de supercondutor de alta-Tc no sistema BSCCO com adição de Pb utilizando Método Pechini de síntese - Aguiar, Felipe Magalhães de [UNESP] (2015)
With high critical temperature superconducting discovered in the 80s, the studies of superconducting materials have intensified in an attempt to obtain materials with Tc increasing, above the temperature of liquid nitrogen (77 K). However, some superconducting materials of high Tc are difficult to be obtained, as in the case of superconducting ceramic compositesof Bi- Sr-Ca-Cu-O (BSCCO) that presents predominant four phases: Bi2Sr2CuO6 (Bi-2201), Bi2Sr2Ca1Cu2O8 (Bi 2212), Bi2Sr2Ca2Cu3O10 (Bi-2223) and Bi2Sr2Ca3Cu4O12 (Bi-2234), with its Tc respectively in the range of 7-22 K, 75-94 K, 100-125 K and 90-100 K. Unfortunately the high-Tc phase (Bi-2223) in this high-temperature superconductor is thermodynamically unstable. One of the used solutions to improve this phase stability is the chemical element substitution. Thus, in this work we study the stabilization of the Bi-2223 phase using the method of chemical element substitution in which the Bi was replaced partially by Pb. For this, the stoichiometry used was Bi2-xPbxSr2Ca2Cu3Oywith x = 0.00; 0.30; 0.35; 0.40; 0.45; 0.50 mol/g. The solutions were prepared by the polymeric precursor method based on the Pechini method. The polymeric resin obtained was thermally treated at 200°C for 10 h.Then the resin was macerated and the powder obtained in this procedure was again thermally treated between 400°C and 810°C. With the resulting powder, pastilles were prepared and soon after were subjected to a new thermal treatment to 845°C for 60 h. Structural characterizations of the samples were investigated by the technique of X-ray diffraction - (XRD); electrical characterization by four-point probe dc conductivity method and chemical characterization by Energy-dispersive X-ray spectroscopy (EDX).The results showed that in the samples prepared with concentrations of 0.00, 0.30 and 0.35 mol/g Pb prevailed the phase Bi -2212, however for the concentration of 0.40 mol/g of Pb the Bi-2223 phase was the...